2020
DOI: 10.3390/languages5040038
|View full text |Cite
|
Sign up to set email alerts
|

Men Finally Got It! Rhotic Assibilation in Mexican Spanish in Chihuahua

Abstract: Rhotic assibilation is a common sociolinguistic variable observed in different Spanish speaking countries such as Argentina, Ecuador, and México. Previous studies reported that rhotic assibilation alternates with the flap and/or with the trill. In this study, we explore three aspects of rhotic assibilation in the Spanish of the state of Chihuahua, Mexico/El Paso, TX, United States: (1) Its diachronic development; (2) the linguistic and social factors that affect this variation and; (3) the possible effect of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 6. Rissel (1989) showed that female speakers favored assibilated variants of /r/ in Mexican Spanish; however, that study included tokens produced in both the phrase-final context and the intervocalic context (for a similar study, see Mazzaro & González de Anda, 2020). …”
mentioning
confidence: 99%
“… 6. Rissel (1989) showed that female speakers favored assibilated variants of /r/ in Mexican Spanish; however, that study included tokens produced in both the phrase-final context and the intervocalic context (for a similar study, see Mazzaro & González de Anda, 2020). …”
mentioning
confidence: 99%
“…In the coastal or lowland areas, the Costeño dialect has extreme /s/ reduction, while, in the interior highlands, including the Andean Highlands, Cachaco features more conservative variants of sibilance maintenance. In both macro-dialects, but particularly in Costeño, jejeo or initial /s/ weakening has been observed (i.e., [he.m Carril 1971;Mazzaro and González de Anda 2020;Bradley and Willis 2012;Willis 2007;Rissel 1989); as well as in Spain (Henriksen and Willis 2010). (d) Vowel reduction in contact with /s/.…”
mentioning
confidence: 99%